Thermal behaviour studies of solid state compounds of cinnamylidenepyruvate with trivalent lanthanides and yttrium (III) in an atmosphere of CO2 - OLIVEIRA, José Dilson Silva de; Fertonani, Fernando Luís [UNESP]; MELIOS, Cristo Bladimiros [UNESP]; Ionashiro, Massao [UNESP] (Editora Unesp, 2002)
Os cinamalpiruvatos de lantanídeos (III) (exceto promécio) e de ítrio (III), foram preparados no estado sólido. A termogravimetria, termogravimetria derivada (TG, DTG), calorimetria exploratória diferencial (DSC), difratometria de raios X e complexometria foram utilizadas para caracterizar e estudar o comportamento térmico desses compostos em atmosfera dinâmica de CO2. Os resultados obtidos mostraram diferenças significativas na estabilidade e na decomposição térmica desses compostos em relação ao estudo do comportamento térmico em atmosfera dinâmica de ar.

Solid state cinnamylidenepyruvate of trivalent lanthanides (except for promethium) and yttrium, were prepared. Thermogravimetry, derivative thermogravimetry (TG, DTG), differential scanning calorimetry (DSC), X-ray diffraction powder patterns and complexometry were used to characterize and to study the thermal behavior of these compounds in a dynamic CO2 atmosphere. The results obtained showed significative differences on the thermal stability and thermal decomposition of these compounds, with regard to the thermal behavior study in a dynamic air atmosphere.
Estudo do comportamento térmico de compostos no estado sólido de cinamalpiruvatos de lantanídeos (III) e de ítrio (III) em atmosfera dinâmica de CO2
Keywords: Lantanídios; ítrio; cinamalpiruvato; atmosfera de CO2; comportamento térmico; Lanthanides and yttrium; cinnamylidenepyruvate; CO2 atmosphere; thermal behavior